Al-Ghazālī’s Epistemic Architecture Of Knowledge In Ihya’ ‘Ulum Al-Din: A Triadic Philosophical Analysis - Mohammad Rozi Indrafuddin; Basuki Basuki (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This article analyzes the epistemological architecture of knowledge in Ihya’ ‘Ulum al-Din, a work by Imam Al-Ghazālī, through ontological, epistemological, and axiological approaches. This study aims to reveal how Al-Ghazālī constructs and organizes a structure of knowledge that integrates rational, spiritual, and ethical dimensions into a single, coherent epistemological framework. This research employs a qualitative research method based on a literature review, utilizing a philosophical and hermeneutic approach to the text of Ihya’ ‘Ulum al-Din, supported by an analysis of classical texts and international journal articles related to Al-Ghazālī’s thought and Islamic epistemology. The research findings indicate that Al-Ghazālī formulates the concept of knowledge as a reality that is not only related to the object of knowledge but also to the existential condition of the knowing subject. Ontologically, knowledge is understood as divine light that radiates into the human heart. Epistemologically, Al-Ghazālī acknowledges three primary pathways to acquiring knowledge: revelation, reason, and kashf or spiritual intuition. Meanwhile, axiologically, knowledge is directed toward fostering moral perfection and drawing humanity closer to God. Thus, the epistemological architecture of knowledge in Al-Ghazālī’s thought demonstrates the integration of the dimensions of sharia, rationality, and spirituality within a holistic system of knowledge. This finding demonstrates the relevance of Al-Ghazālī’s thought in formulating an integrative paradigm of knowledge capable of bridging the dichotomy between religious knowledge and rational knowledge in the context of contemporary scholarship.